Characteristics of Organellar Genomes and Nuclear Internal Transcribed Spacers in the Tertiary Relict Genus Dipelta and Their Phylogenomic Implications - Peng, Fangfang; Zhao, Zhe; Xu, Bei; Han, Jie; Yang, Qian; Lei, Yunjing; Tian, Bin; Liu, Zhan-Lin (Frontiers in Genetics, 2020)
Dipelta (Caprifoliaceae) is a Tertiary relict genus endemic to China, comprising three species with horticultural and medicinal values. For the lack of genomic information, interspecific relationships and divergence times in the genus remain unresolved. In the present study, we assembled and characterised the complete plastomes, the partial mitogenomes and nuclear internal transcribed spacer (ITS) fragments from genome skimming datasets of fourteen Dipelta individuals. The plastomes were conserved in genomic structure, gene order and gene content, but with highly variable repeat sequences. Three genes (rpl23, ycf1, ycf2) were examined with positive selection, and nine divergent hotpot regions (psbL, accD, rpl23, ycf2, ycf3, rbcL-accD, trnI-CAU-ycf2, ndhH-rps15 and rps18 intron) were potentially valuable for DNA barcodes. Contrasted to the variability in plastome sequences, mitogenomes contained 12 protein-coding genes with limited indels and nucleotide substitutions, and no gene was found under positive selection. Genes in organellar genomes tended to have a similar pattern of codon usage bias, with a preference of A/U ending codons. Phylogenetic trees constructed with plastomes, mitogenomes and ITS sequences consistently supported that Dipelta was monophyletic and D. elegans was sister to the other two taxa. Interspecific divergences were estimated at about 33-37 Ma in the Eocene/Oligocene boundary, suggesting the paleo-endemism of the extant species as ‘living fossils’ of the East Asian Flora. Our study well exhibited that genome skimming could provide valuable genomic information to elucidate the evolutionary history of the complex group in a cost-efficient way.